The Evolution Of Public Diplomacy: A New Strategy For Enhancing State Image - Judijanto, Loso; Fadhilah, Nurul (Pt. Anagata Sembagi Education, 2025)
Public diplomacy has undergone a significant transformation in the digital era, becoming an important instrument in building the country's image on the international stage. This research aims to analyze the evolution of public diplomacy and identify new strategies that can be used by countries to improve their image. By leveraging social media and communication technologies, countries can reach international audiences more directly and build inclusive interactions. Approaches that emphasize positive messages, friendship, and two-way dialogue have proven to be more effective in shaping favorable public opinion. In addition, the challenges arising from the spread of disinformation and narrative competition require adaptation of public diplomacy strategies. The research is expected to provide deeper insights into effective public diplomacy practices, strengthen the role of soft powers, and recommend actions that countries can take to strengthen their international image in an ever-changing global context..